Handbook of Agri-Food Law in China, Germany, European Union Food Security, Food Safety, Sustainable Use of Resources in Agriculture (Springer International Publishing, 2018)
This book offers a new and differentiated overview of Agri-Food Law against the background of national and global integration of markets, and compares for the first time important aspects of the agricultural, environmental and food law of China and Germany / the European Union. In addition to the basics, it discusses a wide range of issues, such as the respective legal regulatory structures for food security, food safety, geographical indications of origin, climate protection, fertilizers, plant protection products, genetic engineering, water protection, soil protection, land resources and organic farming. In addition, it addresses key environmental impacts and developments in order to create integrated value chains. The increasing fusion of upstream and downstream areas is becoming apparent from primary production, to the refinement and trade up level, and even to consumption. Agri-Food Law is now productively taking these important developments into account with regard to the aforementioned countries.